2003
DOI: 10.1359/jbmr.2003.18.5.893
|View full text |Cite
|
Sign up to set email alerts
|

Nulliparity and Fracture Risk in Older Women: The Study of Osteoporotic Fractures

Abstract: Whether nulliparity increases fracture risk is unclear from prior studies, which are limited by small samples or lack of measured bone mineral density. No study has evaluated whether the effect of parity differs by skeletal site. We prospectively analyzed the relationship of parity to the risk of incident nontraumatic hip, spine, and wrist fractures in 9704 women aged 65 years or older participating in the Study of Osteoporotic Fractures to determine if parity reduces postmenopausal fracture risk, and if so, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
70
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 39 publications
10
70
5
Order By: Relevance
“…Such relationship has been reported before in most (but not all) prior studies that examined the association between parity and fracture risk. (22)(23)(24) The most frequently discussed hypothesis underlying such association between parity and fracture risk would be that each additional pregnancy contribute to increase the accumulated lifetime exposure to estrogen and thus reduce the subsequent risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Such relationship has been reported before in most (but not all) prior studies that examined the association between parity and fracture risk. (22)(23)(24) The most frequently discussed hypothesis underlying such association between parity and fracture risk would be that each additional pregnancy contribute to increase the accumulated lifetime exposure to estrogen and thus reduce the subsequent risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…This has been examined through numerous epidemiological studies that have ascertained whether parity confers any risk of lower BMD, an osteoporotic level of BMD, or fragility fractures. The majority of such studies have found either a neutral effect of parity (16, (384,397,421,460,625,689,869,997). One of the studies reporting a protective effect of parity was particularly strong because it involved 1,852 twins and their female relatives, including 83 identical twins who were discordant for ever being pregnant (700).…”
Section: Human Datamentioning
confidence: 99%
“…
We thank Drs Robbins, Schott, and Meunier for validating our results that nulliparity increases the risk of hip fracture in older women (1) among their large EPIDOS cohort. The importance of replication among different study settings is a critical piece for scientific proof of causality of any study's initial findings which we endorse.

We now have several additional years of follow-up of the Study of Osteoporotic Fractures cohort (SOF), which now makes the age of our cohort more closely comparable with what Robbins et al presented with EPIDOS.

…”
mentioning
confidence: 61%
“…We thank Drs Robbins, Schott, and Meunier for validating our results that nulliparity increases the risk of hip fracture in older women (1) among their large EPIDOS cohort. The importance of replication among different study settings is a critical piece for scientific proof of causality of any study's initial findings which we endorse.…”
mentioning
confidence: 61%
See 1 more Smart Citation